(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
This project paper aimed at identifying the dimensions for teacher leadership model. The instrument used to measure the dimensions was adapted from Teacher Leadership Self-Assessment (TLSA) by Katzenmeyer and Moller (2009). This measurement tool consists of 47 items distributed into seven dimensions namely 1) self-awareness, 2) leading change, 3) communication, 4) diversity, 5) instructional proficiency and leadership, 6) continuous improvement, and 7) self-organization. This project paper involved 130 teachers of Mara Junior Science Colleges in the state of Kelantan, Malaysia. Structural Equation Modelling technique was utilized to perform the required statistical analysis of the survey data. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were carried out to substantiate the dimensions used. Based on the EFA and CFA, 4 dimensions are relevant for teacher leadership practice in Malaysian setting with 28 items identified to have high value of validity and reliability. The four dimensions are labelled as 1) self-awareness, 2) communication and change, 3) diversity and instructional proficiency, and 4) organized and continuous improvement. These dimensions could be characterized as values or roles of teacher leaders.